2015
DOI: 10.1038/srep15658
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 contributes to the regenerative potential of the mammary epithelium

Abstract: Although best known for its role in bone development and associated structures the transcription factor RUNX2 is expressed in a wide range of lineages, including those of the mammary gland. Previous studies have indicated that Runx2 can regulate aspects of mammary cell function and influence the properties of cancer cells. In this study we investigate the role of Runx2 in the mammary stem/progenitor population and its relationship with WNT signalling. Results show that RUNX2 protein is differentially expressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 57 publications
(102 reference statements)
4
23
0
Order By: Relevance
“…Several signaling pathways have been demonstrated to be involved in fibrogenesis, among them are the TGF-b and WNT/b-catenin pathways (5). Here, we observed that both, TGF-b and WNT/b-catenin activation induce RUNX2 expression, which is in line with previous reports that reported RUNX2 to be a WNT/b-catenin target gene in osteoblastic cells or mammary epithelium (18,39). Interplay between RUNX genes and TGF-b signaling can occur at various levels.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Several signaling pathways have been demonstrated to be involved in fibrogenesis, among them are the TGF-b and WNT/b-catenin pathways (5). Here, we observed that both, TGF-b and WNT/b-catenin activation induce RUNX2 expression, which is in line with previous reports that reported RUNX2 to be a WNT/b-catenin target gene in osteoblastic cells or mammary epithelium (18,39). Interplay between RUNX genes and TGF-b signaling can occur at various levels.…”
Section: Discussionsupporting
confidence: 92%
“…In our experiments, loss of RUNX2 in ATII cells led to decreased expression of the proliferation marker Ccnd1 , further suggesting that increased RUNX2 contributes to fibrogenesis by enhancing epithelial proliferation. In line with these findings, depletion of RUNX2 is associated with reduced regenerative potential in mammary epithelium and interferes with mammary organoid formation (39). Murine RUNX2‐negative breast cancers showed reduced levels of CCND1 and Ki‐67 expression compared to RUNX2‐positive breast cancers (43).…”
Section: Discussionmentioning
confidence: 68%
“…Activation of the PI3K/Akt pathway could lead to activation of ER-activity without oestrogen stimulation, further contributing to cell growth under tamoxifen treatment. Finally, eIF4E might confer tamoxifen resistance via oestrogen receptor independent pathway due to the activity of mTOR and MNK1 [28], one of the downstream modulators being RUNX2 [33] which is found to be important in breast tumour growth and metastasis [34,35]. Moreover, RUNX2 could regulate the WNT/β-catenin and TCF-β signalling pathways, two pathways essential to tamoxifen resistance [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Cyp1aCre; Apc fl/fl ; p21 -/mice (hereafter referred to as CAP) were characterised in the Sansom lab as described previously (31). These mice were crossed with Runx1 fl/fl mice (32) (a kind gift from Dr Nancy Speck, Jax:010673, B6;129-Runx1 tm3.1Spe/ J) and/or Runx2 fl/fl mice (33). Tumour mice (equivalent numbers males/females in each cohort) were monitored for signs of tumour development and subsequently checked 3 times a week for signs of endpoint renal failure (blood in urine, hunching, swollen kidneys) (31).…”
Section: Gem Model Of Kidney Cancermentioning
confidence: 99%